Gene Therapy for Inflammatory Cascade in Intrauterine Injury with Engineered Extracellular Vesicles Hybrid Snail Mucus‐enhanced Adhesive Hydrogels - Xiaotong Peng; Tao Wang; Bo Dai; Yiping Zhu; Mei Ji; Pusheng Yang; Jiaxin Zhang; Wenwen Liu; Yaxin Miao; Yonghang Liu; Shuo Wang; Jing Sun (Advanced Science)
Abstract Early hyper‐inflammation caused by intrauterine injury triggered subsequent intrauterine adhesion (IUA). STAT1‐mediated M1 macrophages are confirmed to secrete pro‐inflammatory cytokines to accelerate inflammatory cascade and IUA formation by multi‐omics analysis and experimental verification. However, clinically used hyaluronic acid (HA) hydrogels are prone to slip out of injury sites due to poor bio‐adhesion properties. Therefore, there are still challenges in applying hydrogels for M1 macrophage intervention in IUA treatment. Herein, an engineered extracellular vesicles (EVs) hybrid snail mucus (SM)‐enhanced adhesive hydrogels to improve bio‐adhesion property is fabricated and M1 macrophage intervention through targeting delivery and STAT1 silencing is achieved. First, inspired by the high bio‐adhesion capacity of SM, SM and gelatin methacrylate (GelMA) solution are mixed to construct GelMA/SM (GS) hydrogel. Then, folic acid‐modified extracellular vesicles (FA‐EVs) are synthesized for targeting the delivery of STAT1‐siRNA. Upon injection of FA‐EVs hybrid GS hydrogel into the uterine cavity, a protective hydrogel layer forms on the surface of injury sites and sustains the release of STAT1‐siRNA‐loaded FA‐EVs to curtail M1 macrophages generation through inhibiting STAT1 phosphorylation, resulting in reduction of myofibroblasts activation and collagen deposition. In addition, the pregnancy rate and the number of fetuses in rats treated with this hydrogel were much higher than those in other groups, suggesting that the hydrogel could promote functional endometrial regeneration and restore fertility. Overall, this study presents a promising strategy for employing FA‐EVs hybrid adhesive hydrogel with superior bio‐adhesion properties and M1 macrophage targeting delivery for IUA treatment and uterus recovery.